Effect of Supplementing Molasses Based Multi-Nutrient Liquid Supplement (MMLS) on Nutrient Intake, Digestibility and Growth Performance of Buffalo Calves - Yengkhom, Rojita; Singh, Putan; Verma, A K; Handique, Bornalee (Indian Journal of Animal Nutrition, 2020)
Twenty-one buffalo calves (111Â±4.53 kg BW, 6-8 months age) were assigned to 3 groups (T1, T2 and T3) consisting of 7 animals each in a completely randomized block design. Concentrate mixture composition was remained the same for all three groups; however, concentrate to wheat straw ratio were 60:40, 50:50 and 40:60 in groups in T1, T2 and T3, respectively. Additional molasses based multi-nutrient liquid supplement (MMLS) was provided in T2 and T3 groups @ 5% and 10% DMI respectively. Daily intake of green oats, dry matter (DM), OM, NDF and ADF did not differ significantly (P>0.05) among groups. However, concentrates and EE intake were significantly (P